Association Between miR-148a and DNA Methylation Profile in Individuals Exposed to Lead (Pb) - Araújo, Marília Ladeira de; Gomes, Bruno Costa; Devóz, Paula Pícoli; Duarte, Nathália de Assis Aguilar; Ribeiro, Diego Luis; Araújo, Adriana Ladeira de; Batista, Bruno Lemos; Antunes, Lusânia Maria Greggi; Barbosa, Fernando; Rodrigues, António Sebastião; Rueff, José; Barcelos, Gustavo Rafael Mazzaron (Frontiers in Genetics, 2021)
Experimental and epidemiologic studies have shown that lead (Pb) is able to induce epigenetic modifications, such as changes in DNA methylation profiles, in chromatin remodeling, as well as the expression of non-coding RNAs (ncRNAs). However, very little is known about the interactions between microRNAs (miRNAs) expression and DNA methylation status in individuals exposed to the metal. The aim of the present study was to investigate the impact of hsa-miR-148a expression on DNA methylation status, in 85 workers exposed to Pb. Blood and plasma lead levels (BLL and PLL, respectively) were determined by ICP-MS; expression of the miRNA-148a was quantified by RT-qPCR (TaqMan assay) and assessment of the global DNA methylation profile (by measurement of 5-methylcytosine; % 5-mC) was performed by ELISA. An inverse association was seen between miR-148a and % 5-mC DNA, as a function of BLL and PLL (β = -3.7; p = 0.071 and β = -4.1; p = 0.049, respectively) adjusted for age, BMI, smoking and alcohol consumption. Taken together, our study provides further evidence concerning the interactions between DNA methylation profile and miR-148a, in individuals exposed to Pb.